Spatio-temporal dynamics of the commercial seabob shrimp Xiphopenaeus kroyeri (Heller, 1862) and physico-chemical parameters in a marine protected area: Changes in abundance and distribution after 20 years - Bernardes, Veronica P. [UNESP] (2022)
Studies comparing parameters before and after the establishment of protected areas in coastal environments allow improvements of management plans and recognition of alterations due to natural or anthropic effects. This study compared spatio-temporal variation in abundance of Xiphopenaeus kroyeri in two equivalent periods. The first period was 12 years before the establishment of the Marine Protected Area and the second was 8 years after. The influence of environmental factors in relation to abundance was also analyzed. Samples were conducted monthly at Ubatuba Bay, Southeast Brazilian coast in period 1 (1995–1996) and 2 (2016–2017). Five transects were sampled using the same methodology, encompassing depths from 5 to 15 meters and areas sheltered or exposed to tidal waves and currents. Abundance varied seasonally. Higher values were obtained in December, March, and June of period 1 and in April and July of period 2. These months correspond to autumn and the beginning of winter. Seasonal fluctuations in abundance seems to be a response to higher and more stable salinity and the efficacy of the closed season (March–May), favoring a higher abundance in the autumn. There was no significant difference of X. kroyeri abundance between periods. Results indicate stability of population density through time in the region, suggesting conservation measurements are aiding species’ protection is spite of a larger fishing fleet. Our study reinforces the importance of measurements to mitigate fishery resources along with other non-commercial species important to preserve local biodiversity.